Contextualizing employability: Do boundaries of self-directedness vary in different labor market groups?. Issue 5 (12th September 2016) - Kovalenko, Maxim; Mortelmans, Dimitri
Abstract : Purpose: Individual employability has become a crucial element in ensuring labor security in flexibilizing labor markets. The importance of agency-side factors as antecedents of employability has been emphasized in the relevant literature, spurring the criticism that some worker groups may be more restricted than others by contextual factors in respect to their employment prospects. The purpose of this paper is to examine empirically how labor market groups differ in what shapes their employability. Design/methodology/approach: The authors used a representative sample of 1, 055 employees to detect differences in the impact of career self-directedness (agency-side) and several contextual factors (structure-side) on employability, comparing workers with and without higher education and workers in and outside managerial positions. Confirmatory factor analysis with subsequent tests of invariance was used. Findings: Results confirm that employability is affected both by contextual factors and by self-directedness. No significant differences were observed between the compared groups in the extent to which self-directedness and the contextual factors influence employability. An important finding is that self-directedness itself is affected by preceding career history (career mobility and previous unemployment), which may suggest a vicious-circle relationship between past and future career precariousness. Practical/implications: The findings support the view prevailing in policy circles that fostering agency-side factors such as self-directedness is instrumental toward achieving higher employment security. At the same time, individual agency cannot replace traditional policy measures in tackling structural labor market inequalities. Originality/value: This study uses robust methodology and a representative respondent sample to statistically disentangle the effects of agency and context on employability. Its key contribution pertains to the explicit comparison of different worker groups, with separate contrasts on each model parameter.